Bioactive glass based scaffolds incorporating gelatin/manganese doped mesoporous bioactive glass nanoparticle coating. Issue 12 (15th August 2019) - Nawaz, Qaisar; Ur Rehman, Muhammad Atiq; Roether, Judith A.; Yufei, Liu; Grünewald, Alina; Detsch, Rainer; Boccaccini, Aldo R.
Abstract: We investigated the bioactivity and cytocompatibility of 45S5 bioactive glass (BG) based scaffolds coated with a composite layer formed by gelatin and manganese doped mesoporous bioactive glass nanoparticles (Mn-MBGNs). The scaffolds were prepared using the foam replica method, and they were further coated with Mn-MBGNs/gelatin via dip coating. The synthesized scaffolds were characterized in relation to morphology, porosity, mechanical stability, bioactivity and cell biology behavior using osteoblast-like (MG-63) cells. The scaffolds were highly porous with interconnected porosity, and a suitable pore structure was maintained even after the Mn-MBGNs/gelatin coating. Energy-dispersive X-ray spectroscopy (EDX) confirmed the presence of Mn-MBGNs in the coatings. Moreover, the presence of gelatin was confirmed by Fourier transform infrared spectroscopy (FTIR). The coated scaffolds exhibited in-vitro bioactivity in simulated body fluid comparable to that of uncoated BG scaffolds. Finally, Mn-MBGNs/gelatin coated scaffolds were shown to be non-cytotoxic to MG-63 cells. Hence, the results presented here confirm that the novel Mn containing scaffolds can be considered in the field of biologically active ion releasing scaffolds for bone tissue engineering applications. Highlights: 45S5 BG scaffolds coated with gelatin/manganese doped mesoporous bioactive glass nano particles via dip coating. Mn-MBGNs/gelatin coating improved compression strength. Mn-MBGNs/gelatin coated scaffolds were bioactive upon immersion in SBF. Coated scaffolds were non-cytotoxic to MG-63 cells.